Genotypic variation for root pulling resistance in potato and its relationship with yield under water deficit stress - Ekanayake, I.J.; Midmore, D.J. (Springer, 1992)
An extensively distributed root system may reduce the probability of crop failure during periods of restricted water supply . A quantitative measure of root distribution in the soil profile, i .e . pulling resistance of roots (PR), was tested at two moderately droughted tropical field sites . A total of 250 genotypes were evaluated for PR, 45 days after planting and for tuber yield at harvest at separate sites and years . The need to use genotypes adapted to a specific location for comparisons, across sites or seasons was shown by the results of a random analysis of variance model partitioning across site-season, location, and year effects for PR and tuber yield . A combined PR and growth analysis on 31 early-maturing clones, 7 of which had tubers at the time of sampling, gave significant correlations between PR and root length, dry weight of pulled and residual roots, plant height, number of stems, and in the case of the 7 genotypes with tubers, tuberlet weight and number . A regression model to predict PR based on growth analysis data is presented . Neither tuberlet weight nor number contributed significantly to the prediction once root characters and vigour-related characters were incorporated . Variation for PR among clones was significant and the means ranged from 0 kg/plant to 37 kg/plant during the 3 trials . High PR was evident in both early and late maturing clones . Drought resistance (DR), defined as high yielding ability and high PR under water deficit conditions, of the clones Huinkul and MS-35.22 .R was superior to that of the high-yielding and adapted LT-7 check, while moderate levels of DR were confirmed for the clones BR-63 .15, Cruza 27, Haille, and MEX-21 . Tuber yield and PR under moderate drought were significantly correlated (r = 0 .569***), which suggests that the PR method can be utilized to assist in the selection of high-yielding, drought resistant, potato genotypes adapted to tropics .